1980
DOI: 10.1126/science.6243190
|View full text |Cite|
|
Sign up to set email alerts
|

Human Rotavirus Type 2: Cultivation in Vitro

Abstract: A strain of type 2 human rotavirus (Wa) was grown to relatively high titer through 14 passages in primary cultures of African green monkey kidney (AGMK) cells. This passage series was initiated with virus that had been passaged 11 times serially in newborn gnotobiotic piglets. In contrast, virus present in the stool of patient Wa as well as virus from the first, second, or third passage in piglets could not be propagated successfully in African green monkey kidney cells. Prior to each passage in cell culture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(159 citation statements)
references
References 9 publications
1
156
0
2
Order By: Relevance
“…Similar studies now underway revealed that the Wa strain, serotype 1, subgroup II of human rotavirus (Wyatt et al, 1980) and the human-bovine reassortant virus DSI made by H. B.…”
Section: (Accepted 28 November 1985)mentioning
confidence: 81%
“…Similar studies now underway revealed that the Wa strain, serotype 1, subgroup II of human rotavirus (Wyatt et al, 1980) and the human-bovine reassortant virus DSI made by H. B.…”
Section: (Accepted 28 November 1985)mentioning
confidence: 81%
“…The Wa strain of human rotavirus (Wyatt et al 1980) and the MA-104 line of embryonic rhesus monkey kidney cells were used throughout this study. The techniques used for cell culture and virus growth ) and virus quantitation (Raphael, Sattar & Springthorpe, 1985) (NBC).…”
Section: Cells and Virusmentioning
confidence: 99%
“…Additional studies were aimed at comparing the reactivity of the hybridoma preparations with other rotaviruses, namely the human Wa strain (Wyatt et al, 1980) and the simian rotavirus (SAI 1). As shown in Fig.…”
Section: Isolation and Characterization Of Anti-rotavirus Immunoglobumentioning
confidence: 99%